Role of the competitive microbial flora in the radiation-induced enhancement of ochratoxin production by Aspergillus alutaceus var. alutaceus NRRL 3174. - Chelack, W S (1991)
The radiation sensitivity and the toxigenic potential of conidiospores of the fungus Aspergillus alutaceus var. alutaceus were determined after irradiation with 60Co gamma rays and high-energy electrons. Over the pH range of 3.6 to 8.8, the doses required for a 1 log10 reduction in viability based on the exponential portion of the survival curve ranged from 0.21 to 0.22 kGy, with extrapolation numbers (extrapolation of the exponential portion of the survival curve to zero dose) of 1.01 to 1.33, for electron irradiation, and from 0.24 to 0.27 kGy, with extrapolation numbers of 2.26 to 5.13, for gamma irradiation. Nonsterile barley that was inoculated with conidia of the fungus and then irradiated with either electrons or gamma rays and incubated for prolonged periods at 28 degrees C and at a moisture content of 25% produced less ochratoxin A with increasing doses of radiation. Inoculation of barley following irradiation resulted in enhanced ochratoxin levels compared with unirradiated controls. In these experiments, inoculation with 10(2) spores per g produced greater radiation-induced enhancement than inoculation with 10(5) spores per g. There was no radiation-induced enhancement when the barley was surface sterilized by chemical means prior to irradiation. These results are consistent with the hypothesis that a reduction in the competing microbial flora by irradiation is responsible for the enhanced mycotoxin production observed when nonsterile barley is inoculated with the toxigenic fungus A. alutaceus var. alutaceus after irradiation.